A phyllocladiferous new species of Phyllanthus (Phyllanthaceae) from Minas Gerais, Brazil - Orlandini, Priscila; Cordeiro, Inês; Lombardi, Julio Antonio; Zavatin, Danilo Alvarenga; Souza, Vinicius Castro (Phytotaxa, 2024)
We describe a new phyllocladiferous species of Phyllanthus, which is endemic to the Minas Gerais state, Brazil, and is found within the Serra Nova State Park. This new species has cylindrical phylloclades, like those of P. choretroides, another endemic species in Minas Gerais, and P. goianensis and P. chapadensis, both exclusive to the state of Goiás. However, we present distinct characteristics that enable a clear differentiation between these species, related to the aspect of ramification of the phylloclades, morphology of stipules and sepals and characteristics of the extrastaminal disk. Additionally, we provide illustrations, photographs, distribution map, conservation status data and taxonomic comments of the new species.